Modeling of Subsea Control Module using Agito SimulationX - Muhamad Isfan Imanullah b Adnan, Muhamad Isfan I (Universiti Teknologi Petronas, 2012)
This thesis describes the modeling and simulation for subsea control module. For new developer, a better understanding on how the system works is needed to ensure that the system will meet all design specifications and reduced the risk and cost associated with installation and commissioning. Hence, simulating a model of subsea control module provide engineers with ability to do multiple scenario of gate valve or production valve behavior based on its changing parameter. The methodology for this project involves collection of technical details and data regarding subsea control module, identify elements of control, arrangement of elements, and subsea control module design parameters. Simulation result shows that the gate valve is fully open at 0.203m within 11.332 seconds. This will be useful if decision to change the subsea control module parameter was done and needs to do the sensitivity analysis arise.